Squamous cell carcinoma of the tongue in patients older than 45 years - Constantino Ledesma-Montes (Brazilian Oral Research, 2018)
Abstract: This study aims to evaluate the clinicopathological features, TNM status, AJCC staging and behavior of squamous cell carcinoma of the tongue (SCCT) in patients older than 45 years. The files of the Department of Pathology of the Hospital General de México were reviewed and all cases of SCCT in patients older than 45 years were selected. Clinicopathological features, treatment, follow-up, microscopic diagnosis, and IJCC and TNM staging were retrieved. Complete data from 60 cases were evaluated. They were more common in males (mean age = 63.9 years). Unexpectedly a high rate of tumors (38.3%) were in the base of the tongue (BT). Moderately and poorly differentiated SCCT were the most common. 16.7% presented lymph node invasion, 15% were recurrent tumors and BT carcinomas recurred more frequently. A high rate (81.7%) were stage II and 48.3% were low-risk patients. SCCTs in the studied population displayed different clinico-pathological and behavioral features compared with worldwide data. Our results suggest that BT tumors should be treated more aggressively than those in the mobile tongue. BT located tumors were more frequent than previously published. Additional frequency studies will define outcomes in age cohorts with a consensus cut-off for young and elderly populations. More population-based studies should be performed in Latin American regions to acquire accurate data on SCC incidence in elder subpopulations and to identify precisely the etiological factors in these patients.